Pengaruh Seni Melipat Kertas dalam Meningkatkan Motorik Halus Anak Usia 5-6 Tahun di TK Insan Cemerlang Kota Makassar - Nunung Amriani; Musfira Musfira; Sri Suflianti Romba (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to test and find out the influence of the art of folding paper in improving fine motor skills in early childhood aged 5-6 years at Insan Cemerlang Kindergarten, Makassar City. This type of research is quantitative with an experimental approach with a one-group pretest-posttest design. The subjects in this study consisted of 17 children aged 5-6 years in the B1 group. The collection technique in this study uses test performance, observation, documentation and also instruments of children's checklist sheets with indicators of achievement of child development based on the Minister of Education and Culture Regulation No. 17 of 2023. Data analysis was carried out a non-paramentric test with the Wilcoxon Signed Rank Test. The results of this study showed that the pre-test score was 12.7 and increased to the post-test score of 17.1 after being given the art of folding paper (origami). Based on the results of the analysis of the Wilcoxon Signed Rank Test, the Z value is 3,630 with the Asymp.Sig (2-tailed) significance of 000, obtained from a probability below 0.05 or p < 0.05 then Ho is rejected. This is based on probability decision-making: if the probability (Asymp.Sig) < 0.05 then Ho is rejected and Ha is accepted and if the probability (Asymp.Sig) is > 0.05 then Ho is accepted and Ha is rejected. So we can conclude that it shows a significant difference between pre-test and post-test. Thus it shows that there is an influence of the art of folding paper in improving fine motor skills in early childhood in Insan Cemerlang Kindergarten in Makassar City.